Green approaches to biocomposite materials science and engineering - Verma, Deepak, 1983-; Jain, Siddharth, 1984-; Zhang, Xiaolei, 1986-; Gope, Prakash Chandra (Engineering Science Reference, 2016)
"This book explores timely research on the various available types of natural fibers and the use of these fibers as a sustainable alternative to synthetic fibers and polymers by emphasizing research-based solutions for sustainability across various industries"--Provided by publisher.